Outcomes of same-day discharge in bariatric surgery - Cooper, Sydney; Patel, Shivam; Wynn, Matthew; Provost, David; Hassan, Monique (Surgical endoscopy, 2024)
Background Restrictions during the COVID-19 pandemic influenced a shift to same-day discharge in bariatric surgery. Current studies show conflicting findings regarding morbidity and mortality. We aim to compare outcomes for same-day discharge versus admission after bariatric surgery. Methods Subjects included patients who underwent primary laparoscopic or robotic-assisted sleeve gastrectomy or Roux-En-Y gastric bypass at an academic center. The inpatient group included patients discharged postoperative day one, and the outpatient group included patients discharged on the day of surgery. Primary outcomes included the number of emergency room visits, reoperations, IV fluid treatments, readmissions, and mortality within 30 days. Secondary outcomes were morbidity, including skin and soft tissue infection, pulmonary embolism, and acute kidney injury. Results 1225 patients met the inclusion criteria. In the gastric sleeve group, 852 subjects were outpatients and 227 inpatients. In the gastric bypass group, 70 subjects were outpatients, and 40 were inpatients. The mean age was 44.63 (17.38–85.31) years, and the mean preoperative BMI was 46.07 ± 8.14 kg/m 2 . The subjects in the outpatient group had lower BMI with fewer comorbidities. The groups differed significantly in age, BMI, and presence of several chronic comorbidities. The inpatient and outpatient groups for each surgery type did not differ significantly regarding reoperations, IV fluid treatments, or 30-day mortality. The inpatient sleeve group demonstrated a significantly higher readmission percentage than the outpatient group (4.6% vs 2.1%; p = 0.02882). The inpatient bypass group showed significantly greater ER visits (21.7% vs 10%; p = 0.0108). The incidence of adverse events regarding the secondary outcomes was not statistically different. Conclusion Same-day discharge after bariatric surgery is a safe and reasonable option for patients with few comorbidities.